The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ar.1110
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal development of the human mandible

Abstract: In an effort to better understand the interrelationship of the growth and development pattern of the mandible and condyle, a sequential growth pattern of human mandibles in 38 embryos and 111 fetuses were examined by serial histological sections and soft X-ray views. The basic growth pattern of the mandibular body and condyle appeared in week 7 of fertilization. Histologically, the embryonal mandible originated from primary intramembranous ossification in the fibrous mesenchymal tissue around the Meckel cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 36 publications
6
99
0
5
Order By: Relevance
“…The mandibular growth pattern is characterized by intramembranous ossification of the mandibular body and endochondral ossification of the condyle (Lee et al, 2001). The mammalian mandible is a complex morphological structure consisting of multiple morphogenetic components that form the final structure (Atchley, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular growth pattern is characterized by intramembranous ossification of the mandibular body and endochondral ossification of the condyle (Lee et al, 2001). The mammalian mandible is a complex morphological structure consisting of multiple morphogenetic components that form the final structure (Atchley, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In our results, radiographic density level at the MS of the mandible gradually increased from 16 weeks to 28 weeks. Lee et al (2001) suggested that the genioglossus muscle was attached to the connective tissue of Meckel's cartilage in the early stage (12 weeks gestation) and masseter and suprahyoid muscles were not attached in this stage. However, tendon of muscle fiber in human hyoid muscles (digastric and geniohyoid muscles) was inserted into the periosteum and endosteum connective tissue of immature and mature bone at the medial region of the mandible at 28 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular symphysis (MS) (Lee et al, 2001) undergoes a different ossification process to that of the mandibular body (Bareggi et al, 1994). In the formation of human mandible, the mental protuberance comes from fibrous cartilage in the syndesmosis and synostosis (Sperber, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since amputated urodele limbs know how to do this, unraveling how they of the first pharyngeal arch at 5-6 weeks post-conception. 72,73 Ossification begins at each side of the mandible in the region of the bifurcation of the inferior alveolar nerve and artery into mental and incisive branches. The ossification spreads upwards, dorsally and ventrally to form a trough for the developing teeth, the body and the ramus of the mandibles, respectively.…”
Section: Radiograms Of Control (A B A' and B') And Ra-treated (Cmentioning
confidence: 99%